The Role of Entrepreneurial Leadership and Competence in Enhancing MSME Performance: A Case Study in Jember Regency - Septy Holisa Umamy; Gardina Aulin Nuha (Universitas Bina Sarana Informatika, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic growth, job creation, and social security, particularly in Jember Regency, where MSMEs constitute a significant portion of the business sector. However, various challenges, such as leadership effectiveness, entrepreneurial competence, and motivation, may impact their overall performance. This study aims to examine the influence of entrepreneurial leadership and competence on MSME performance, with entrepreneurial motivation as a mediating variable. A quantitative explanatory research design was employed, involving a survey of 101 MSME owners in Jember Regency using purposive sampling. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that entrepreneurial leadership significantly affects MSME performance, whereas entrepreneurial competence and motivation do not show a direct impact. However, both leadership and competence positively influence entrepreneurial motivation. Furthermore, motivation does not mediate the relationship between leadership or competence and MSME performance. These findings suggest that MSME performance is shaped not only by internal factors such as leadership and competence but also by external influences, including access to capital, government policies, and infrastructure support. Future research should explore additional variables such as innovation, digital marketing, and business strategies to provide a more comprehensive understanding of MSME growth and sustainability.